Atypical Ocular Coloboma in Tuberous Sclerosis-2: Report of Two Novel Cases. Issue 3 (September 2021) - Bacci, Giacomo M.; Polizzi, Silvio; Mari, Francesco; Conti, Valerio; Caputo, Roberto; Guerrini, Renzo
Abstract : Abstract: Tuberous sclerosis complex (TSC) is an autosomal dominant multisystemic disorder caused by mutations in either TSC1 or TSC2 genes and is characterized by hamartomas in multiple organs. The most frequent and best-known ocular manifestation in TSC is the retinal hamartoma. Less frequent ocular manifestations include punched out areas of retinal depigmentation, eyelid angiofibromas, uveal colobomas, papilledema, and sector iris depigmentation. In this article, we report 2 patients carrying known pathogenic variants in the TSC2 gene who exhibited an atypical, unilateral, iris coloboma associated with localized areas of retinal dysembryogenesis.